Two-Photon Holographic Stimulation of ReaChR - Chaigneau, Emmanuelle; Ronzitti, Emiliano; Gajowa, Marta A.; Soler-Llavina, Gilberto J.; Tanese, Dimitrii; Brureau, Anthony Y. B.; Papagiakoumou, Eirini; Zeng, Hongkui; Emiliani, Valentina (Frontiers in Cellular Neuroscience, 2016)
Optogenetics provides a unique approach to remotely manipulate brain activity with light. Reaching the degree of spatiotemporal control necessary to dissect the role of individual cells in neuronal networks, some of which reside deep in the brain, requires joint progress in opsin engineering and light sculpting methods. Here we investigate for the first time two-photon stimulation of the red-shifted opsin ReaChR. We use two-photon (2P) holographic illumination to control the activation of individually chosen neurons expressing ReaChR in acute brain slices. We demonstrated reliable action potential generation in ReaChR-expressing neurons and studied holographic 2P-evoked spiking performances depending on illumination power and pulse width using an amplified laser and a standard femtosecond Ti:Sapphire oscillator laser. These findings provide detailed knowledge of ReaChR's behavior under 2P illumination paving the way for achieving in depth remote control of multiple cells with high spatiotemporal resolution deep within scattering tissue.